Hemorrhage After Endovascular Recanalization in Acute Stroke: Lesion Extent, Collaterals and Degree of Ischemic Water Uptake Mediate Tissue Vulnerability - Nawabi, Jawed; Kniep, Helge; Schön, Gerhard; Flottmann, Fabian; Leischner, Hannes; Kabiri, Reza; Sporns, Peter; Kemmling, André; Thomalla, Götz; Fiehler, Jens; Broocks, Gabriel; Hanning, Uta (Frontiers in Neurology, 2019)
Background and Purpose Intracranial hemorrhage (ICH) remains a major complication of endovascular treatment (ET) in acute stroke. The aim of this study was to identify clinical and imaging predictors for ICH in patients with acute ischemic stroke undergoing successful ET. Methods We performed a retrospective analysis of patients with large vessel occlusion in the anterior circulation who underwent successful ET at our university medical center between 2015 and 2018. ICH was diagnosed on non-enhanced CT and a binary outcome was defined: ICH occurrence in the immediate post-interventional phase within 12-36 hours (yes/no). The impacts of clinical, radiological, and interventional parameters on outcome were assessed in univariable and multivariable logistic regression models. Results 107 patients fulfilled the inclusion criteria. 37 (34.6%) showed an ICH of which 7 (6.5%) patients were diagnosed as symptomatic and 30 (28.04%) as asymptomatic. Multivariable regression analyses identified a lower ASPECTS (adjusted odds ratio (OR) 1.95, 95%CI: 1.4-3.63, P<0.037), low collateral score (adjusted OR 0.12, 95%CI: 0.03-0.49, P<0.003) and high Net Water Uptake (NWU) (adjusted OR 1.56, 95%CI: 2.34-1.03, P<0.007) as independent predictors of ICH after successful ET. Subgroup analysis of SICH demonstrated congruent results, despite the relatively low number of patients. Conclusions CT-based quantitative NWU, ASPECTS and collateral score mediate tissue vulnerability and are reliable independent predictors of a bleeding event after successful ET. This imaging-based prediction model might be useful for early stratification of patients at high risk of a bleeding event after ET, especially with low ASPECTS.